2014
DOI: 10.1071/an14220
|View full text |Cite
|
Sign up to set email alerts
|

Growth, feed intake and maternal performance of Angus heifers from high and low feed efficiency selection lines

Abstract: Feed conversion efficiency is an important factor affecting profitability for cow-calf production systems. One method of characterising feed conversion efficiency is by calculating residual feed intake (RFI), the difference between measured and expected feed intakes. A high RFI value indicates low feed efficiency while a low RFI value indicates high feed efficiency. The present experiment used 49 Angus heifers sired by Angus bulls selected for high or low RFI. The progeny were bred on commercial farms and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In terms of milk composition, Montanholi et al (2013b) reported a negative relationship between RFI and milk lactose concentration (r = −0.29) in beef cows but no association with other milk constituents. Consistent with reported results on cow milk yield, calf pre-weaning growth was not associated with maternal status for RFI (Lawrence et al, 2013;Morris et al, 2014). Given that maternal weaning weight is representative of dam milk yield and, at a genetic level, Crowley et al (2011) found no relationship between maternal weaning weight and RFI of growing males, these findings corroborate Feed efficiency in beef cattle the absence of a phenotypic association between cow RFI ranking and milk yield or progeny performance pre-weaning.…”
Section: Maternal Traits and Fertilitysupporting
confidence: 88%
See 3 more Smart Citations
“…In terms of milk composition, Montanholi et al (2013b) reported a negative relationship between RFI and milk lactose concentration (r = −0.29) in beef cows but no association with other milk constituents. Consistent with reported results on cow milk yield, calf pre-weaning growth was not associated with maternal status for RFI (Lawrence et al, 2013;Morris et al, 2014). Given that maternal weaning weight is representative of dam milk yield and, at a genetic level, Crowley et al (2011) found no relationship between maternal weaning weight and RFI of growing males, these findings corroborate Feed efficiency in beef cattle the absence of a phenotypic association between cow RFI ranking and milk yield or progeny performance pre-weaning.…”
Section: Maternal Traits and Fertilitysupporting
confidence: 88%
“…In terms of reproductive performance, no differences were found between high and low-RFI beef females with regard to pregnancy, calving and/or weaning rates (Basarab et al, 2007;Morris et al, 2014;Jones et al, 2016), although in other studies a lower pregnancy and calving rate (Basarab et al, 2011) and lower weaning rate (Copping et al, 2016;Hebart et al, 2016) was observed for low-RFI females. Donoghue et al (2011) and Hebart et al (2016) reported that low-RFI females calved later in the calving season than their high-RFI contemporaries; however, this was not evident in other studies (Morris et al, 2014). Crowley et al (2011) reported a negative, but not statistically significant, genetic correlation (r = −0.29) between age at first calving and RFI status in beef cattle.…”
Section: Maternal Traits and Fertilitymentioning
confidence: 56%
See 2 more Smart Citations
“…The pregnancy, calving and weaning rates, days to calving, calf weight per cow exposed, and milk production evaluated over three reproductive cycles were similar, with high RFI (most efficient) cows exhibiting more subcutaneous fat at the beginning of the breeding season. Morris et al [26] also demonstrated that heifers born to sires with low EBV (most efficient) and high EBV (least efficient) for RFI did not differ in terms of pregnancy rate in the first or second breeding season, calf weight at birth or weaning, or milk production at 50, 100 and 150 days of lactation. These results encourage the use of negative RFI animals for sire and dam replacement in the herd, since these animals had decreased DMI with similar overall performance, making them more profitable due to lower input costs.…”
Section: Plos Onementioning
confidence: 98%